Tyger bright - McCarthy, T. C. (Baen, 2022)
"San Kyarr is a noviate within a secretive holy order tasked by Fleet to infiltrate the home world of mankind's most dangerous enemy: the Sommen. If caught, her mission will bring war to Earth-long before humanity is ready to confront this implacable enemy. To make matter worse, a competing faction within Fleet learns of the clandestine assignment and sends San's own brother to destroy her. Now, San must deal with heartrending human treachery and intrigue. Most of all, she must adapt and survive as she find herself transforming into a being that is perhapes beyond human nature itself."--